PENINGKATAN KEMANDIRIAN MELALUI KEGIATAN PEMBELAJARANPRACTICAL LIFE - RANTINA, MAHYUMI (Program Studi Magister Pendidikan Anak Usia Dini, 2015)
Abstract: The purpose of this research was to determine the process of implementation of the learning activities of practical life. The research was conductedon agroup ofkindergartenwith anumber of14in March andApril 2015.The method used in this research is an action research which refers to the model of a Classroom Action Research Kemmis and Mc. Taggart consist of four phase: planning, action, observation and reflection. This research consist of two cycles, each cycle consist of 8 times in actions.Data analysis usingquantitative and qualitative data.Quantitativedata analysis wasdone usingdescriptive statisticsto dataattainment of self-relianceof childreninpre-cycle, the first cycleandsecond cycle. While thequalitative analysiscarried out onthe data offield notesandinterview transcripts. The results showedan increase inthe child's self-relianceafterlearning activities ofpracticallife. Dataattainment of self-relianceof childreninpre-recorded cycle of47.99%.The data isincreased to69.31% at the end ofthe firstcycle, and furtherincreased to85.01% at the end ofthe second cycle. Keywords: Early Chilhood, self-reliance, learning activities of practical life